The Effectiveness of Storyboards on Vocational High School Students’ Speaking Skills - Hanifah, Apriia Putri; Aminin, Zainul (Universitas PGRI Adi Buana Surabaya, 2026)
Vocational high school students often face difficulties in developing their English-speaking performance in classroom learning. Integrating digital visual media may support students in practicing speaking more effectively. Therefore, this study investigates the effectiveness of Digital Storyboard using the Storyboard That platform to improve vocational high school students’ speaking skills. This study employed a one-group pre-experimental design involving students from a public vocational high school in Sidoarjo. Students’ speaking performance was measured using pre-test and post-test assessments and analyzed using the Wilcoxon Signed-Rank test and effect size analysis. The results revealed a significant improvement in students’ speaking scores, with the mean score increasing from 45.06 in the pre-test to 57.06 in the post-test. The statistical analysis indicated a significant difference between the two tests (Z = -5.233, p < .001), with a moderate-to-large effect size (Cohen’s d = 0.71). These findings suggest that digital storyboard media can effectively support the improvement of vocational high school students’ speaking performance in English learning.